Latitudinal clines in sexual selection, sexual size dimorphism and sex‐specific genetic dispersal during a poleward range expansion. Issue 6 (21st April 2021) - Dudaniec, Rachael Y.; Carey, Alexander R.; Svensson, Erik I.; Hansson, Bengt; Yong, Chuan Ji; Lancaster, Lesley T.
Abstract: Range expansions can be shaped by sex differences in behaviours and other phenotypic traits affecting dispersal and reproduction. Here, we investigate sex differences in morphology, behaviour and genomic population differentiation along a climate‐mediated range expansion in the common bluetail damselfly ( Ischnura elegans ) in northern Europe. We sampled 65 sites along a 583‐km gradient spanning the I. elegans range in Sweden and quantified latitudinal gradients in site relative abundance, sex ratio and sex‐specific shifts in body size and mating status (a measure of sexual selection). Using single nucleotide polymorphism (SNP) data for 426 individuals from 25 sites, we further investigated sex‐specific landscape and climatic effects on neutral genetic connectivity and migration patterns. We found evidence for sex differences associated with the I. elegans range expansion, namely (a) increased male body size with latitude, but no latitudinal effect on female body size, resulting in reduced sexual dimorphism towards the range limit, (b) a steeper decline in male genetic similarity with increasing geographic distance than in females, (c) male‐biased genetic migration propensity and (d) a latitudinal cline in migration distance (increasing migratory distances towards the range margin), which was stronger in males. Cooler mean annual temperatures towards the range limit were associated with increased resistance to gene flow in both sexes. Sex ratios became increasingly male biased towards the range limit, and there was evidence for a changed sexual selection regime shifting from favouring larger males in the south to favouring smaller males in the north. Our findings suggest sex‐specific spatial phenotype sorting at the range limit, where larger males disperse more under higher landscape resistance associated with cooler climates. The combination of latitudinal gradients in sex‐biased dispersal, increasing male body size and (reduced) sexual size dimorphism should have emergent consequences for sexual selection dynamics and the mating system at the expanding range front. Our study illustrates the importance of considering sex differences in the study of range expansions driven by ongoing climate change. Abstract : Male and female damselflies have different ecological, demographic and genetic responses during an ongoing, climate change‐mediated range expansion. Accounting for sex‐specific responses is likely to be important for accurately predicting how a species will respond to climate change, and persist in novel environments following range expansion.